2016
DOI: 10.24914/jeb.v17i3.311
|View full text |Cite
|
Sign up to set email alerts
|

Penyusunan Model Program Corporate Social Responsibility (CSR) di Perguruan Tinggi Kota Salatiga Dalam Upaya Meningkatkan Intake Perguruan Tinggi

Abstract: Corporate Social Responsibility (CSR) is one of the promotion techniques done by a Public Relations in higher education

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The results of previous studies (Cahya et al, 2019;Suhardiyah & Nurdina, 2019;Harjanto, 2019;Mustika & Sahudra, 2018;Asy'ari, 2015;Wijaya & Krismiyati, 2016;Rumambi & Lintong, 2017;Symaco & Tee, 2019;Atiqah, 2019) regarding to the importance of social and environmental aspects for higher education were agreed by the answers of all the respondents in this study. They all consider that social and environmental aspects are crucial for higher education to pay attention to and measure its performance.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The results of previous studies (Cahya et al, 2019;Suhardiyah & Nurdina, 2019;Harjanto, 2019;Mustika & Sahudra, 2018;Asy'ari, 2015;Wijaya & Krismiyati, 2016;Rumambi & Lintong, 2017;Symaco & Tee, 2019;Atiqah, 2019) regarding to the importance of social and environmental aspects for higher education were agreed by the answers of all the respondents in this study. They all consider that social and environmental aspects are crucial for higher education to pay attention to and measure its performance.…”
Section: Discussionsupporting
confidence: 80%
“…Higher education is required to make a real contribution to solving social problems that exist in society to create a sustainable future (Wijaya & Krismiyati, 2016). This opinion was agreed upon by all respondents (BAN 01-02, REK 01, DEK 01, PRO 01-02, LEM 01-02).…”
Section: Crucial Roles Of Social and Environmental Perpectivesmentioning
confidence: 96%
See 1 more Smart Citation
“…In Indonesia, a study of a university in Surabaya indicated that its CSR consists of 33 activities which can be grouped into three themes such as economy, social, and environment [11]. In addition, a study in 12 universities and 12 high schools in Solo found that CSR relates to community training through small and medium organizations, community services, lecturers teaching at high schools, teacher and administration staff training, and scholarships [12]. It indicates that social responsibility focus and implementation in higher education institution are internal policy [13] at BSP, the social responsibility commitment is conducted through a declaration as a centre of technology with Green Tourism concept.…”
Section: B Green Tourism As Social Responsibility Initiativementioning
confidence: 99%